Who are to support the aged in rural China? The study of people's willingness to purchase socialized care service and its influencing factors - Baozhong, Su; Yuheng, Li; Xiaodong, Zheng (Journal of rural studies, 2022)
The ageing of the rural population and the citizenization of the rural-urban migrated population have brought unprecedented pressure and challenges to Chinese farmers' old-age care. Socialized old-age care services are a necessity to fulfil the service needs of farmers' old-age care. This study examines the farmers' willingness to pay for socialized old-age care and its influencing factors. Based on field survey data, this paper employs the descriptive statistics method and a binary logistic model to determine and analyze the influencing factors of rural residents' willingness to pay for rural socialized old-age care. We observed the following: rural residents generally have a willingness to pay for rural socialized old-age care services but are subject to their own economic conditions, traditional concepts, and external supply conditions. The influencing factors of rural socialized old-age care include the marital status, self-care ability, enrollment in the New Old-Age Insurance System for Rural Residents, proportion of migrating children, health status, and the population living in the same household. The marital status, the enrollment of New Old-Age Insurance System for Rural Residents, and proportion of migrating children have a positive facilitating effect on willingness to pay. The self-care ability, health status, and the number of residents in the same household have a reverse effect. Considering the willingness to pay, the already-old are more affected by the traditional old-age care concept and more dependent on their children. For the not-yet-old, factors that contribute to transferring old-age care responsibilities to themselves and society have become more significant, which contributes to the existing literature. •Rural residents generally have a WTP for rural socialized old-age care.•The marital status, enrollment of the insurance, and proportion of children migrating have a positive effect on the WTP.•Self-care ability, health status, and number of residents in the same household have the reverse effect on the WTP.•The ‘age’ and ‘generations’ are not significant influencing factors of the WTP for rural socialized old-age care.•The not-yet-old are relatively less affected by the traditional concept of old-age care and more dependent on their children.